IgA sérica, secretora, IgE total e estado nutricional em crianças com infecções por enteroparasitas - Dantas, Valéria Cristina Ribeiro (2003)
Infections for intestinal parasites are one of the main morbidade causes in humans and, its relationships with socioeconomic levels and hygiene conditions in countries in development are already very established. Many works, even so, they are being accomplished to elucidate the complex interactions among nutrition, these infections and answer imunológica, because it is seen that malnutrition commits the immunity increasing the susceptibilidade for infectious diseases and these for its time can harm the state human nutricional. It is known that sponge helmínticos they stimulate synthesis of IgE so much policlonal as specific for the same ones and that IgA secretora, main imunoglobulina of defense of the mucous ones, can act against protozoa as the Giardia lamblia and against helmintos as Trichuris tichiura and Strongyloides stercorales. Some studies show that the malnutrition energy protéica influences in the production of these answers, but some authors show results divergentes. In this work it was evaluated the levels of total IgE, IgA sérica and secretora, contagem of sanguine eosinófilos, levels of proteins séricas and state nutricional, in 103 children of low socioeconomic level, to discover a correlation between those and infection for enteroparasitas. They participated in the study children of both sexes, with age of 3 to 6 years, visitors of the same creche and residents in a neighborhood with precarious hygiene conditions and basic saneamento, in the city of Christmas. The obtained results showed that the faulty environmental and socioeconomic conditions favored to a high infection frequency for enteroparasitas, mainly Trichuris trichiura and Ascaris lumbricoides between the helmintos and Endolimax sleep and Giárdia lamblia among the protozoa. Light malnutrition without deficit protéico was observed in 30% of the children, which didn't also present significant deficiencies of IgA sérica and secretora. The sponged children